Comparison of the safety and efficacy of fixed-dose combination of arterolane maleate and piperaquine phosphate with chloroquine in acute, uncomplicated Plasmodium vivax malaria: a phase III, multicentric, open-label study. (December 2016) - Valecha, Neena; Savargaonkar, Deepali; Srivastava, Bina; Rao, B.; Tripathi, Santanu; Gogtay, Nithya; Kochar, Sanjay; Kumar, Nalli; Rajadhyaksha, Girish; Lakhani, Jitendra; Solanki, Bhagirath; Jalali, Rajinder; et al.
Abstract Background Chloroquine has been the treatment of choice for acute vivax malaria for more than 60 years. Malaria caused byPlasmodium vivax has recently shown resistance to chloroquine in some places. This study compared the efficacy and safety of fixed dose combination (FDC) of arterolane maleate and piperaquine phosphate (PQP) with chloroquine in the treatment of uncomplicated vivax malaria. Methods Patients aged 13–65 years with confirmed mono-infection ofP. vivax along with fever or fever in the previous 48 h were included. The 317 eligible patients were randomly assigned to receive FDC of arterolane maleate and PQP (n = 159) or chloroquine (n = 158) for 3 days. Primaquine was given as an anti-relapse measure on day 3 and continued for 14 consecutive days. Primary efficacy analysis included assessment of the proportion of aparasitaemic and afebrile patients at 72 h. Safety endpoints were analysis of adverse events, vital signs, laboratory data, and abnormalities on electrocardiograph. Patients participated in the study for at least 42 days. Results In per protocol population, the proportion of aparasitaemic and afebrile patients at 72 h was 100 % (140/140) in the FDC of arterolane maleate and PQP group, and 99.3 % (145/146) in the chloroquine group (Fisher, p > 0.9999). In intent to treat population, the corresponding value was reported to be 96.9 % (154/159) in the FDC of arterolane maleate and PQP group and 98.7 % (156/158) in the chloroquine group (Fisher, p = 0.4479). The median parasite clearance time was 24 h in FDC of arterolane maleate and PQP group and 26 h in chloroquine group (Log-rank, p = 0.2264). Similarly, median fever clearance time was 24 h in both the groups (Log-rank, p = 0.7750). In PP population, day 28 cure rates were 100 % in both the groups (95 % CI (96.52, 100.0 for FDC of arterolane maleate and PQP and 96.73, 100.0 in chloroquine group)). Incidence of adverse events was 82.4 % in the FDC of arterolane maleate and PQP group and 85.4 % in the chloroquine group. Most of the adverse events were mild to moderate in intensity. The commonly reported clinical adverse events in the FDC of arterolane maleate and PQP versus chloroquine group were vomiting (5.0 vs 5.1 %), headache (1.3 vs 3.2 %) and prolonged QT (1.9 vs 3.2 %). No deaths were reported. The pharmacokinetic analysis indicates that arterolane maleate is well absorbed and has a relatively short t1/2 of 3.2 h. Piperaquine is also well absorbed after oral administration with a t1/2 of about 228.33 h. Conclusions The study showed that FDC of arterolane maleate and PQP effectively cured vivax malaria and attained acceptable level of cure up to day 28. Both the groups showed similar safety profile. Trial Registration Clinical Trial Registry India: CTRI/2011/11/002129